Symptomatic lithospheric drips triggering fast topographic rise and crustal deformation in the Central Andes - Julia Andersen; Oguz H. Göğüş; Russell N. Pysklywec; Tasca Santimano; Ebru Şengül Uluocak (Communications Earth & Environment, 2022)
Several central Andean basins may have formed from the coupling of crustal deformation to dripping of the upper mantle lithosphere, according to three- dimensional scaled analogue experiments